PENGARUH PELATIHAN DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KOMPETENSI - Arief Purwanto; Gatot Nugroho (IAIN Batusangkar, 2021)
This article aims to explain the direct influence of the variables of training, empowerment, competence, and performance. And the role of competence mediating variables. The method used is quantitative–explanatory. The population and sample are 54 respondents. They are collecting data using a questionnaire—data analysis using smart-PLS 3. The results show directly that training has not been able to improve employee performance. Meanwhile, empowerment can improve employee performance, as well as competence, can improve performance. In the indirect research results, first, it is known that competence in complete mediation can mediate the effect of training on employee performance. Second, competence in partial mediation can intervene in the influence of empowerment on employee performance